The Dynamics of Sharia Mutual Fund Market Share in Indonesia: The Role of the Sharia Stock Market and the Influence of Conventional Competition: Dinamika Pangsa Pasar Reksa Dana Syariah di Indonesia: Peran Pasar Saham Syariah dan Pengaruh Kompetisi Konvensional - Ahyak; Sulhan (Program Studi Ekonomi Syariah & LP2M STAI Az-Zain Sampang, 2025)
This study examines the dynamics of the sharia mutual fund market share in Indonesia from 2010 to 2025. Amid the rapid growth of Islamic finance, the research addresses the empirical gap concerning factors influencing the competitiveness of sharia mutual funds against conventional funds and the sharia stock market. Using annual data from the Financial Services Authority (OJK), a multiple linear regression with time series data is employed. The dependent variable is the sharia mutual fund market share, while independent variables include sharia stock market capitalization (ISSI), net asset value (NAB) of conventional mutual funds, and the number of sharia mutual funds. The analysis reveals that all variables are non-stationary at level but stationary at first difference, with a high explanatory power (R² = 0.970). Results indicate that the number of sharia mutual funds significantly and positively affects market share, whereas sharia stock market capitalization and conventional fund competition show no significant impact. This study’s novelty lies in focusing on internal capital market competition as determinants of market share. The findings offer strategic implications for regulators and industry stakeholders to develop adaptive, sustainable policies fostering an inclusive Islamic finance ecosystem